Numerical study of the influence of hydrofoil hydrodynamic performance considering near-free surface - Yuanhui Wei; Jianing Zhang; Kaihao Liu; Jiazhen Pan; Lei Zhang; Weimin Chen; Qingshan Zhang (Brodogradnja)
Bionic flapping hydrofoil motion is increasingly used in bionic underwater robots. However, many scholars have focused their attention on the navigation problem in deep-water environments, thus ignoring changes in the hydrodynamics of hydrofoils under the action of the near-free-surface effect. This paper studies and explores the hydrofoil motion in near-free surfaces through the RANS viscous flow numerical simulation method, combined with overset mesh and adaptive mesh technology. Three different forms of motion are studied respectively, including a stationary fixed, a single-degree-of-freedom pitch and a two-degree-of-freedom heaving-pitching coupled hydrofoil. The effects of varying the immersion depth d on the lift and thrust generated were analyzed. Results indicate noticeable differences in the free surface action among different motion forms. When the water depth is less than one chord length C, the lift and thrust of the three motion forms decreased rapidly decrease. When d/C=1~1.5, the static fixed hydrofoil lift and thrust gradually approach the deep-water state. When d/C>2, the pitching motion of a single degree of freedom also tends to be stable. The two-degree-of-freedom motion is d/C>3. This finding shows that the effect of the near-free surface is closely related to the vertical motion. The greater the vertical motion is, the more severe the effect.